Testing the practical aspects of therapeutics by objective structured clinical examination. - Langford, N; Landray, M; Martin, U; Kendall, M; Ferner, R (2004)
Medical students need to have a sound theoretical knowledge of pharmacology and a training in the practical aspects of therapeutics in order to prescribe effectively, safely and rationally when they qualify. Students have traditionally sat written exams and the practical aspects have been largely ignored. At the University of Birmingham we set up an objective structured clinical examination (OSCE) style examination to test the practical aspects of therapeutics. Over the last 2 years, 434 students have been examined in this way to determine competency in various clinical skills including, for example prescription writing, the drawing up and giving of injections, setting up nebulizers, and patient counselling about drug effects. Over that time we found the therapeutics OSCE to be feasible and useful. It has demonstrated serious practical deficiencies that were not apparent from written examinations in some students' ability to prescribe and administer drugs. Since its introduction, performance in the OSCE has improved. Whether this will result in safer and more effective prescribing in the preregistration house officer year has not been formally evaluated but it appears that they approach this aspect of patient care with greater confidence than graduates from other schools.